Competitive Advantage: An Analysis of the Role of Data-Driven Innovation Capabilities and Marketing Agility - Wahyudi, Wahyudi; Heridiansyah, Jefri; Prabowo, Catur; Harminingtyas, Rudika; Widowati, Maduretno (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
This study examines the role of data-driven innovation capabilities (DDIC) and marketing agility (MA) in enhancing competitive advantage (CA) among SMEs in Central Java. Using a quantitative approach and PLS-SEM analysis, the research tests two main hypotheses regarding the influence of DDIC on MA and the effect of MA on CA. The findings reveal that DDIC significantly strengthens MA, which subsequently improves firms’ competitive advantage. These results highlight the strategic importance of leveraging data, technology, market orientation, and organisational adaptability in responding to market dynamics. The study also emphasises that firms must invest in digital infrastructure and talent capabilities to fully optimize data-driven innovation efforts. Although limited by its geographical scope and selected variables, the research provides avenues for future studies, including incorporating objective performance indicators and conducting cross-cultural comparisons to enhance generalizability